Ray Tracing Algorithm to Simulate Laser-Cut Panel Light-Redirecting Elements - Ribeiro, Pedro Vitor Sousa; Cabús, Ricardo Carvalho (Journal of daylighting, 2023)
Daylighting simulation software is an important tool to improve the quality of building design and to improve the quality of the built environment. For its application to correspond to reality, its algorithm needs to reflect real behaviour in the best possible way. This paper aims to propose an algorithm to simulate the behaviour of fenestration complex systems, such as the laser-cut panel, based on ray tracing techniques. The algorithm was developed in MatLab as an add-on for the TropLux software, using the physical formulas associated with the concepts of daylight coefficients, ray tracing and Monte Carlo method. After validation it is possible to realize that the developed algorithm can simulate the light behaviour through complex fenestration systems using plane-based modelling with precision and accuracy. The tests using laser cut panel, ordinary glass and prismatic glass obtained behaviour close to that observed in similar measurements and algorithms.